2006
DOI: 10.1053/j.gastro.2006.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Cytologic Techniques for the Detection of Malignant Pancreatobiliary Strictures

Abstract: Background & Aims-Two advanced cytologic techniques for detecting aneuploidy, digital image analysis (DIA) and fluorescence in situ hybridization (FISH) have recently been developed to help identify malignant pancreatobiliary strictures. The aim of this study was to assess the clinical utility of cytology, DIA, and FISH for the identification of malignant pancreatobiliary strictures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
236
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(254 citation statements)
references
References 29 publications
12
236
1
5
Order By: Relevance
“…The technique offers the clinician almost definitive diagnostic certainty when positive for malignancy (specificity 96 -100%) but has a poor ability to detect malignancy (sensitivity 18 -57%) (de Bellis et al, 2002b;Baron et al, 2004;Harewood et al, 2004;Moreno Luna et al, 2006). This proof of principle study has shown that the sensitivity of the automated immunofluorometric Mcm5 test on bile aspirates for detecting pancreaticobiliary malignancy was superior (four times more at the 1000 cells per well cut point) to that of brush cytology, while maintaining a high specificity.…”
Section: Discussionmentioning
confidence: 86%
“…The technique offers the clinician almost definitive diagnostic certainty when positive for malignancy (specificity 96 -100%) but has a poor ability to detect malignancy (sensitivity 18 -57%) (de Bellis et al, 2002b;Baron et al, 2004;Harewood et al, 2004;Moreno Luna et al, 2006). This proof of principle study has shown that the sensitivity of the automated immunofluorometric Mcm5 test on bile aspirates for detecting pancreaticobiliary malignancy was superior (four times more at the 1000 cells per well cut point) to that of brush cytology, while maintaining a high specificity.…”
Section: Discussionmentioning
confidence: 86%
“…Conversely, individual tests generally have suboptimal performance characteristics. For example, conventional brush cytology has excellent specificity (nearly 100%) but limited sensitivity (ranging from 18%‐40%) in diagnosing CCA 15, 35, 36, 37, 38, 39. Similarly, while serum CA 19‐9 has a reported sensitivity and specificity of 79% and 98%, respectively, at a cut‐off value of 130 U/mL,40 its levels may become elevated in the setting of nonmalignant obstruction or acute cholangitis, and it is undetectable in Lewis blood antigen‐negative patients (and remains so even in the presence of CCA) 41.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) has been increasingly used to facilitate the identification of neoplastic cells in cytologic specimens [27] . In one study, 20% of patients with cholangiocarcinoma missed by conventional cytology were identified by FISH without affecting the specificity [28] . Several studies have evaluated the diagnostic yield of endoscopic US fine needle aspiration in patients with biliary strictures [29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%